2012
DOI: 10.1007/s11064-012-0794-1
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of Fish Oil on Acrylamide Induced Oxidative Stress and Neuronal Apoptosis in Cerebral Cortex

Abstract: Acrylamide (ACR) is a known industrial toxic chemical that produce neurotoxicity characterized by progressive neuronal degeneration. This study was designed to investigate the protective effect of fish oil on ACR-induced neuronal damage in Wistar rats. ACR enhances the production of reactive oxygen species and potentially affects brain. ACR administered rats showed increased levels of lipid peroxidative product, protein carbonyl content, hydroxyl radical and hydroperoxide which were significantly modulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 49 publications
5
37
1
Order By: Relevance
“…In contrast, the brain antioxidant enzymes; GST, GPx, and GR activities and GSH content significantly decreased in the ACR-treated rats when compared with the control group (Table 4). These results are inconsistent with those of Lakshmi et al (2012) who reported that the ACR-intoxicated rats exhibited an increase in the LPO, protein carbonyl, hydroxyl radical, and hydroperoxide levels with subsequent decrease in the activities of enzymatic antioxidants, and the level of GSH. ACR promotes the generation of reactive oxygen species (ROS) and the depletion of antioxidants, leading to neurodegeneration (Zhu et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, the brain antioxidant enzymes; GST, GPx, and GR activities and GSH content significantly decreased in the ACR-treated rats when compared with the control group (Table 4). These results are inconsistent with those of Lakshmi et al (2012) who reported that the ACR-intoxicated rats exhibited an increase in the LPO, protein carbonyl, hydroxyl radical, and hydroperoxide levels with subsequent decrease in the activities of enzymatic antioxidants, and the level of GSH. ACR promotes the generation of reactive oxygen species (ROS) and the depletion of antioxidants, leading to neurodegeneration (Zhu et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…These results were in agreement with Lakshmi et al (2012) who reported that the activity of AChE was decreased in the ACR-induced rats. Free radical formation by ACR may upset the prooxidant/antioxidant balance within the brain, which could be one of the reasons for the decrease in the AChE activity (Tsakiris et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…The current study was designed to investigate the ameliorating effect of DSS on ACR induced neurotoxicity and neuronal degeneration in trigeminal ganglia -as a part of peripheral nervous system -and cerebellar cortex -as a part of CNS -in rats. The results are explained by previous studies [9,19]. They proved that ACR enhances the production of reactive oxygen species which play a role in the oxidative stress and potentially affect the brain.…”
Section: Discussionsupporting
confidence: 77%
“…ACR shows its toxic effect on both central nervous system and peripheral nervous system [16]. Both oxidative stress and apoptosis play a key role in ACR-induced toxicity [17][18][19]. ACR-induced lipid peroxidation is the reason forreproductive, and neurotoxic properties [21,22], induces apoptosis in cerebral cortex [19], and efficiently binds to the brain [23].…”
Section: Introductionmentioning
confidence: 99%
“…Both oxidative stress and apoptosis play a key role in ACR-induced toxicity [17][18][19]. ACR-induced lipid peroxidation is the reason forreproductive, and neurotoxic properties [21,22], induces apoptosis in cerebral cortex [19], and efficiently binds to the brain [23]. In both laboratory animals and humans, ACR neurotoxicity is characterized by ataxia and distal skeletal muscle weakness [24].…”
Section: Introductionmentioning
confidence: 99%